COMPARISON OF THE AMOUNT OF APICAL EXTRUSION OF BACTERIA FOLLOWING THE USE OF DIFFERENT INSTRUMENTATION TECHNIQUES – AN IN VITRO STUDY - Hegde, Mithra N.; Thatte, Snehal (Journal of Health and Allied Sciences NU, 2011)
Objectives: The objective of this study is to compare the amount of extrusion of bacteria beyond the apical foramen after instrumentation with Crown down and Step-back techniques using a manual and engine driven nickel-titanium instrumentsMaterials and Methods: Seventy-five mandibular premolars with similar dimensions were used for the study. Access cavities prepared and root canals contaminated with a suspension of Enterococcus faecalis. The contaminated teeth were then divided into three experimental groups. Group 1(Crowndown group) divided into two: Group 1–A Hand files: root canals were instrumented using K-files and Group 1B – Rotary files: root canals were instrumented using ProTaper instruments. Group II (Step-back group) divided into two: Group II A– Hand files: root canals were instrumented using K-files and group II B–Rotary files: the root canals were instrumented using Light Speed LSX instruments. Group III (control group): no instrumentation was done.Bacteria were extruded after preparation were collected into vials, microbiological samples were incubated in culture media for 24hrs. The CFUs were determined for each sample. The data obtained was analyzed using the Kruskal-Wallis one way analysis of variance and Mann-Whitney U-tests.Result: There was a significant difference in the amount of bacteria extruded by both Crowndown and Step-back. The Step- back hand method extruded significantly more bacteria when compared with Crowndown hand technique.Conclusion: All instrumentation techniques extruded intracanal bacteria apically. There was a significant difference in both the engine driven instrumentation techniques, while the hand instrumentation by Step-back extruded more bacteria.
Keywords: apical extrusion; bacteria; crowndown; step- back